PENERAPAN PEMBAGIAN HARTA WARISAN DI ANTARA AHLI WARISNYA DZAWIL FURUD MENUNJUKKAN BAHWA ANGKA PEMBILANG LEBIH BESAR DARI ANGKA PENYEBUT PASAL 192 KOMPILASI HUKUM ISLAM (KHI) - Syuhada' Syuhada' (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2020)
Islamic inheritance, Farâ'idh or Islamic inheritance regulates various matters in the distribution of inheritance to those entitled to receive it on the basis of the provisions stipulated in the Qur'an, the sunnah of the Holy Prophet. and scholars agreement. The maker of farâ'idh or Islamic inheritance is Allah. The object is a relic. the goal can be to give heir rights to inheritance in accordance with the guidelines of Islamic law based on the Al-Qur'an, Al-Hadit, Al-?Ijmâ and Al-Qiyâs. Inheritance in Islam contains the rule of law regarding the transfer of corpses property definitively and contains a pure package from Allah SWT (tauqifi), that is why the verses of the Qur’an that explain about inheritance are not many, only three places regulate in detail, detail, and clear. Even so al-Qur'an still provides ijtihâd space in understanding the Qur'anic texts related to the explanation of inheritance law. KHI article 192 " Apabila dalam pembagian warisan di antara para ahli warisnya Dzawil furud menunjukkan bahwa angka pembilang lebih besar dari angka penyebut, maka angka penyebut dinaikkan sesuai dengan pembilang, dan baru sesudah itu harta warisnya dibagi secara aul menurut angka pembilang ". The heirs in KHI article 192 are heirs only consisting of Dzawil furud, the heirs who receive a definite share. The portion received by Dzawil furud is a definite part, namely: 1 / 2,14.1 / 8, and 2/3, 1 / 3.1 / 6), the part must be given by Dzawil furud in full, meaning that it should not be added let alone reduced, but the other side of inheritance is not sufficient to be given to the heirs in full, therefore, done in Aul. The Aul case in article 192 KHI only applies to the heirs of Dzawil furud, the heirs who received the definite portion that has been explained by Allah. in the Qur'an definitively In Aul's case the gains of each of Dzawil furud were reduced and decreased according to their share, even though the reduction was different but the fact of the reduction was the same. Because both are reduced and the same reduction is still a fair category. The Aul case in article 192 KHI was included in the domain of fiqh so that it was included in the category of ijtihad problems but there was still a chance of a difference